2013
DOI: 10.1038/labinvest.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of autotaxin/lysophospholipase D expression in intestinal vessels in aggravation of intestinal damage through lymphocyte migration

Abstract: Lysophosphatidic acid (LPA) has a critical role in lymphocyte migration to secondary lymphoid organs. Autotaxin (ATX)/lysophospholipase D, in the vascular endothelium, is the main enzyme involved in LPA production. Whether ATX is involved in pathological lymphocyte migration to the inflamed mucosa has not been studied. We investigated the involvement of ATX in inflammatory bowel disease patients and two murine models of colitis. Tissue samples were obtained by intestinal biopsies from patients with Crohn's dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 27 publications
9
45
0
Order By: Relevance
“…Consistent with the expression of autotaxin in the inflamed intestinal mucosa of IBD patients and the involvement of the autotaxin-LPA pathway in pathologic lymphocyte migration in animal models of colitis (Hozumi et al, 2013), we have demonstrated a significant dose-dependent inhibition of the disease activity score by compound-1in the DSS-induced model of IBD. The inhibitor also resulted in a partial reversal of colon-length shortening observed in the model.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with the expression of autotaxin in the inflamed intestinal mucosa of IBD patients and the involvement of the autotaxin-LPA pathway in pathologic lymphocyte migration in animal models of colitis (Hozumi et al, 2013), we have demonstrated a significant dose-dependent inhibition of the disease activity score by compound-1in the DSS-induced model of IBD. The inhibitor also resulted in a partial reversal of colon-length shortening observed in the model.…”
Section: Discussionsupporting
confidence: 86%
“…Autotaxin expression is significantly higher in the actively inflamed mucosa compared with the quiescent mucosa in the same patient (Hozumi et al, 2013). In addition, autotaxin in the vascular endothelium has been shown to be involved in pathologic lymphocyte migration to the inflamed mucosa in two murine models of colitis, namely the CD4 1 CD25 -T-cell transfer model and the dextran sodium sulfate (DSS)-induced colitis model (Hozumi et al, 2013). Pharmacological intervention with bithionol, a weak inhibitor of autotaxin, has been shown to decrease lymphocyte infiltration and ameliorate colitis in the T-cell transfer model.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Metabolism and adipogenesis studies in mice indicate that ATX and its product, LPA, participate in energy homeostasis and obesity control ( 56-59, 104, 124, 125 ), which when dysregulated can lead to infl ammation and cancerogenesis. In addition to data showing association of ATX activity with rheumatoid arthritis ( 134 ), liver infl ammation ( 135,136 ), fi brosis development (137)(138)(139)(140)(141), and infl ammatory bowel disease ( 142 ), it has been proposed that ATX is mechanistically involved in linking both hepatitis C to hepatocellular carcinoma ( 143 ) and Epstein-Barr virus positivity to anaplastic large-cell and Hodgkin lymphoma development ( 107 ). MMTV-driven transgenic overexpression of either ATX or each of the three major LPA receptors (LPA1, -2, and -3) causes late-onset, invasive, and metastatic breast cancer development in mammary glands of mice ( 144 ).…”
Section: Role In Physiology and Cancer Pathophysiologymentioning
confidence: 99%
“…ATX is produced in response to infl ammation to mediate wound repair. If the infl ammation is not resolved, then high ATX concentrations persist in association with infl ammatory diseases such as arthritis and infl ammatory bowel disease ( 1,7,8 ). In addition, infl ammatory bowel disease and hepatitis can progress to carcinogenesis in these organs ( 1 ).…”
mentioning
confidence: 99%